Phosphoryl Group Exchange between ATP and ADP Catalyzed by H+-ATPase from Oat Roots. - Helguera, G. (1997)
ATP-ADP exchange was estimated in the presence of plasma membrane H+-ATPase of oat (Avena sativa) roots partially purified with Triton X-100 by measuring [14C]ATP formation from [14C]ADP. Most studies were done at 0[deg]C. At pH 6.0 the exchange showed: (a) Mg2+ requirement with a biphasic response giving maximal activity at 152 [mu]M and (b) insensitivity to ionic strength, [Na+], and [K+]. ATP and ADP dependence were analyzed with a model in which nucleotide-enzyme interactions are at rapid-random equilibrium, whereas E1ATP [left right arrow] E1P-ADP transitions occur in steady state. The results indicated competition between ADP and ATP for the catalytic site, whereas ATP interaction with the ADP site was extremely weak. At 0[deg]C the exchange showed a 3-fold pH increase, from pH 5.5 to 9.0. At an alkaline pH the reaction was not affected by sodium azide and carbonyl cyanide p-trifluometoxyphenyl-hydrazone, had a biphasic response to Mg2+ (maximal at 513 [mu]m), and was insensitive to ionic strength. At 20[deg]C ATP-ADP exchange was pH insensitive. At both temperatures ATP hydrolysis displayed a bell-shaped response, with a maximum around pH 6.0 to 6.5. Because no adenylate kinase activity was detected under any condition, these results demonstrate the existence of an ATP-ADP exchange reaction catalyzed by the plant H+-ATPase.